2023
DOI: 10.1021/acsami.2c21620
|View full text |Cite
|
Sign up to set email alerts
|

Dual Single-Atom Moieties Anchored on N-Doped Multilayer Graphene As a Catalytic Host for Lithium–Sulfur Batteries

Abstract: Lithium−sulfur (Li−S) batteries are promising for energy storage, especially in the era of carbon neutrality. Nonetheless, the sluggish kinetics of converting soluble lithium polysulfides into solid lithium sulfide impedes its development. In this work, we design Fe and Co dual single-atom moieties anchored on N-doped multilayer graphene (FeCoNGr) as a catalytic sulfur cathode host for Li−S batteries. With an efficient catalytic role in converting soluble lithium polysulfides into solid Li 2 S, the FeCoNGr-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Based on single-atom catalysts, considering the relatively weak interaction and the small contact area between monatomic sites and substrates, to further enhance the number and load of atomic active sites, metal diatomic sites have attracted increasing attention in recent years as emerging family members of single-atom catalysts. [90,[191][192][193] To date, the research of dual-atom catalysts remains in its infancy, the reported literatures so far mainly focused on heterogeneous diatomic catalysts and heteronuclear diatomic catalysts for M-S batteries. [88,194,195] The S-ion mappings of ToF-SIMS on the top surface of e) FeNC-EEB-1, f) FeNC-EEB-2, and g) FeNC.…”
Section: Metal Diatomic Sites Regulationsmentioning
confidence: 99%
“…Based on single-atom catalysts, considering the relatively weak interaction and the small contact area between monatomic sites and substrates, to further enhance the number and load of atomic active sites, metal diatomic sites have attracted increasing attention in recent years as emerging family members of single-atom catalysts. [90,[191][192][193] To date, the research of dual-atom catalysts remains in its infancy, the reported literatures so far mainly focused on heterogeneous diatomic catalysts and heteronuclear diatomic catalysts for M-S batteries. [88,194,195] The S-ion mappings of ToF-SIMS on the top surface of e) FeNC-EEB-1, f) FeNC-EEB-2, and g) FeNC.…”
Section: Metal Diatomic Sites Regulationsmentioning
confidence: 99%
“…Graphene is a 2D nanosheet of a monolayer, honeycomb-arranged carbon lattice with excellent electrical conductivity, mechanical strength, thermal stability, and high functionalizability, among other properties. 197 Graphene derivatives, such as graphene oxide (GO) and reduced graphene oxide (rGO), have many or some oxygen functionalization and are much more common in literature as they are easier to prepare while sharing similar properties with perfect graphene. 198 As modifiers for commercially available polyolefin separators, graphene and its derivatives reduce the shuttle effect via ionic sieving with controllable pore sizes and enhanced LiPS reduction kinetics owing to increased electron mobility.…”
Section: Carbon-based Modificationsmentioning
confidence: 99%
“…Because of the maximized atomic utilization and excellent catalytic activities, single atoms present accelerated conversion kinetics for sulfur cathodes. Single atoms with Fe [48], Co [86], Ni [87], Cu [88], and W [44] as active sites have been confirmed to be promising electrocatalysts, which considerably restrain the polysulfide shuttling. The coordination environment of single atoms plays a key role in catalytic activities.…”
Section: Gibbs Free Energymentioning
confidence: 99%